Tindak Pidana Penganiayaan Mengakibatkan Matinya Orang Oleh Anak (Studi Kasus Putusan Nomor 1/Pid.Sus-Anak/2020/Pn.Kpn) - Muhammad Hasbi Ashshidiqi; JM Muslimin; Mara Sutan Rambe (JOURNAL of LEGAL RESEARCH, 2021)
This article discusses the conditions and situations where self-defense or self-defense is permitted when faced with a criminal act. This article discusses the terms and limits to which self-defense can be exercised. In addition, because this article discusses cases committed by children, this study will also discuss the Criminal Justice System for Children, starting from the principles to law enforcement against children who commit crimes.This research is a juridical-normative research using a case approach. The data in this study were collected using a literature study. The document that is the source of data in this study is the Decision of the Kepanjen District Court Number 1 / Pid.Sus-Anak / 2020 / PN.Kpn. The results of this study describe the qualifications of an act that is said to be forced defense that exceeds the limit (noodweer excess). In carrying out forced defending that goes beyond the limit, there must be great mental turmoil in addition to other conditions. Extreme mental shock is a condition that affects the mind, such as being very afraid, very panicked, very angry, and very confused. With these conditions, it affects the reason of a maker, so that he cannot possibly think about the consequences of his defense. Therefore, such actions cannot be punished because there are reasons or grounds for forgiveness.